2022
DOI: 10.1038/s41591-022-01694-6
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab plus ipilimumab with or without live bacterial supplementation in metastatic renal cell carcinoma: a randomized phase 1 trial

Abstract: Previous studies have suggested that the gut microbiome influences the response to checkpoint inhibitors (CPIs) in patients with cancer. CBM588 is a bifidogenic live bacterial product that we postulated could augment CPI response through modulation of the gut microbiome. In this open-label, single-center study (NCT03829111), 30 treatment-naive patients with metastatic renal cell carcinoma with clear cell and/or sarcomatoid histology and intermediate- or poor-risk disease were randomized 2:1 to receive nivoluma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
191
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 269 publications
(199 citation statements)
references
References 45 publications
5
191
2
1
Order By: Relevance
“… 34 , 35 It has been shown that CBM588 modulates composition of gut microbiome and increases resident Bifidobacterium in a murine model and cancer patients. 8 , 22 In consistent with the results reported by Dizman and Meza et al ., 22 our study showed that resident Bifidobacterium tends to increase in the gut of lung cancer patients who received CBM588 of the presence of C. butyricum in the gut microbiome. These lines of evidence support the hypothesis that CBM588 may have the potential to improve the therapeutic efficacy of ICB through the modulation of gut microbiota.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“… 34 , 35 It has been shown that CBM588 modulates composition of gut microbiome and increases resident Bifidobacterium in a murine model and cancer patients. 8 , 22 In consistent with the results reported by Dizman and Meza et al ., 22 our study showed that resident Bifidobacterium tends to increase in the gut of lung cancer patients who received CBM588 of the presence of C. butyricum in the gut microbiome. These lines of evidence support the hypothesis that CBM588 may have the potential to improve the therapeutic efficacy of ICB through the modulation of gut microbiota.…”
Section: Discussionsupporting
confidence: 92%
“…CBM588 has been shown to increase resident Bifidobacterium , which is known as a potentially beneficial bacteria for immunotherapy. 4 , 22 , 34 , 35 16S rRNA gene sequencing of fecal samples showed a 1.8-fold non-significant increase in Bifidobacterium in cancer patients who received CBM588 ( Figure 7(c )). Patients who received CBM588 had lesser relative abundance of potentially harmful oral-related bacteria for immunotherapy, Atopobium ( Figure 7(d )).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations